Pulp Diagnostic Tests - Kara Tuncer, Aysun; Kayatas, Müzeyyen; Tuncer, Safa (My University, 2014)
Pulp diagnostic tests evaluate the neuropsychological status and blood flow of the pulp. These tests can be used in conjunction with other clinical tests, such as periodontal probing, percussion, palpation, mobility, and anesthesia, during diagnostic tests. In clinical practice, it is important to determine the pulp condition in deciding the correct treatment to be applied. The aim of this review is to provide information about the pulp diagnostic tests that are used in dental practice and to generalize the correct use of these tests.
Keywords: Review; Dental pulp; dental pulp tests; tooth